Desnutrición infantil y su influencia al proceso de aprendizaje de los niños de la escuela fiscal mixta "Daniel Rodas Bustamante" de la ciudad de Loja - Sarango Robles, Andrea del Carmen (2014)
Malnutrition is an indicator that reflects the cumulative effects of a poor diet over time, as the adequate nutritional status is important for intellectual development, especially at school age and early adolescence (6-12 years) since both stages have remarkable physical and psychological changes. To determine the impact of malnutrition on learning and academic achievement is a priority in our community. A quantitative, descriptive and transversal study was conducted to determine the influence of child malnutrition in the learning process of children from school Rhodes Daniel Bustamante, with sample of 44 students, for this use anthropometric indicators, growth patterns published by the World Health Organization, as well as formulas and Waterlow classification. As a result it was found that 88% of children / as are within the normal range, 4% are wasted and 8% severely wasted; with average weight and height below the normal parameters, affecting all ages and male gender with 66%. 64% of students have acute malnutrition, chronic malnutrition and 34% only 2% chronic malnutrition has worsened; that significantly affects learning and academic performance that shows that 45% of students obtained lower grades averaging 7 corresponds to fair or poor and 32% between 7-8 points corresponding to good. Most are malnourished students with academic performance between good and regular, which suggests that malnutrition negatively affects school performance. Keywords: Malnutrition, learning.